(untitled) (Medicine Today, 2022)
Introduction: Incidence of ACS is increasing in developing countries like Bangladesh. Many factors can influence in hospital outcome of NSTEMI Patient. Platelet count is one of them. The aim of present study was by measuring platelet count to detect the severity of NSTEMI patients and their in hospital outcome. Objective: The aim of present study was to observe the impact of platelet counts on in hospital outcome of NSTEMI. Materials and Methods: The study was conducted in Shahid Sheikh Abu Naser Specialized Hospital, Khulna from January 2021 to November-2021. NSTEMI Patient Presented within 24 hours of chest pain was included in this study. Data were collected by direct interview from Patient and venous blood was drawn for platelet count. Continuous data were expressed as mean ±SD. Categorical data were analyzed with x2 test. Student’s ‘t’ test was used for analysis of Continuous variables. Comparision between groups was done by unpaired t-test. Multiple logistic regression analysis was done to determine the association between lower platelet counts and adverse hospital events in NSTEMI patients. P-values <0.05 were be considered statistically significant. Results: 100 Patients are included in this study. They are devided into two groups. Group-1 having platelet count <200000/cmm) and Group-II having platelet count > 200000/cmm. Bleeding, Q-wave MI, arrythmia and heart failure were significantly (P<0.05) higher in group-I but stroke and death were similar in both groups. Conclusion: Lower platelet count in NSTEMI patient is associated with adverse in-hospital outcome. Medicine Today 2022 Vol.34(2): 125-129